A Zymomonas mobilis Mutant with Delayed Growth on High Glucose Concentrations - Douka, Eugenia (American Society for Microbiology, 1999)
Exponentially growing cells of Zymomonas mobilis normally exhibit a lag period of up to 3 h when transferred from 0.11 M (2%) to 0.55 M (10%) glucose liquid medium. A mutant of Z. mobilis (CU1Rif2), fortuitously isolated, showed more than a 20-h lag period when grown under the same conditions, whereas on 0.55 M glucose solid medium, it failed to grow. The growth of CU1Rif2 on elevated concentrations of other fermentable (0.55 M sucrose or fructose) or nonfermentable (0.11 M glucose plus 0.44 M maltose or xylose) sugars appeared to be normal. Surprisingly, CU1Rif2 cells grew without any delay on 0.55 M glucose on which wild-type cells had been incubated for 3 h and removed at the beginning of their exponential phase. This apparent preconditioning was not observed with medium obtained from wild-type cells grown on 0.11 M glucose and supplemented to 0.55 M after removal of the wild-type cells. Undelayed growth of CU1Rif2 on 0.55 M glucose previously conditioned by the wild type was impaired by heating or protease treatment. It is suggested that in Z. mobilis, a diffusible proteinaceous heat-labile factor, transitionally not present in 0.55 M glucose CU1Rif2 cultures, triggers growth on 0.55 M glucose. Biochemical analysis of glucose uptake and glycolytic enzymes implied that glucose assimilation was not directly involved in the phenomenon. By use of a wild-type Z. mobilis genomic library, a 4.5-kb DNA fragment which complemented in low copy number the glucose-defective phenotype as well as glucokinase and glucose uptake of CU1Rif2 was isolated. This fragment carries a gene cluster consisting of four putative coding regions, encoding 167, 167, 145, and 220 amino acids with typical Z. mobilis codon usage, −35 and −10 promoter elements, and individual Shine-Dalgarno consensus sites. However, strong homologies were not detected in a BLAST2 (EMBL-Heidelberg) computer search with known protein sequences.